Foreign Languages in Primary education: an opportunity under construction (Itinerarios Educativos, 2024)
Between December 2022 and September 2023, the self–convened movement of Santa Fe Foreign Language Teachers was part of the curriculum development process for Primary Education in the province. This article intends to describe the vicissitudes of this process, examine the school teachers’ perspectives and expectations about the prospective curriculum and present the main decisions made by the writing team. Likewise, the need to expand the teaching of Foreign Languages in the primary level is highlighted, bearing in mind that the issue is now under evaluation by the new educational officials.
Keywords: foreign languages